Pengembangan Bahan Ajar Berbasis RME Berbantuan Macromedia Flash untuk Meningkatkan Kemampuan Pemecahan Masalah Matematisdan Self-Efficacy Siswa - Siregar, Sry Laila Angelina; Mulyono, Mulyono; Surya, Edy (Mathematics Education Study Program, 2023)
The use of macromedia flash as a learning medium is useful for teachers as an aid in preparing teaching materials and organizing learning. It is hoped that through research on the development of RME-based teaching materials assisted by Macromedia Flash this can be an alternative to realizing a quality learning process and is also expected to improve students' problem-solving skills and self-efficacy. This research has several objectives: (1) To produce RME-based teaching materials assisted by Macromedia Flash to improve students' mathematical problem-solving skills and Self-Efficacy which are valid, practical and effective; and (2) to determine the increase in students' mathematical problem-solving abilities and self-efficacy by using the developed Macromedia Flash-assisted RME-based teaching materials. The type of research conducted is development research. This study used the Thiagarajan 4-D development model and researchers developed teaching materials based on a realistic mathematical approach. The subjects in this study were grade 7th students of East Halongonan One Roof Public Middle School 4 for the 2020/2021 academic year. In the first trial, there were 30 students in grades 7-3 and in the second trial, there were 30 students in grades 7-2.The results showed that: (1) There was an increase in students' mathematical problem solving ability and self-efficacy by using developed Macromedia Flash assisted RME-based teaching materials; and (2) RME-based teaching materials assisted by macromedia flash to improve students' mathematical problem-solving skills and self-efficacy developed in this study already meet valid, practical and effective criteria.